Phenotypic and Genotypic Screening for VIM and IMP-Type Metallo-β-Lactamases in Acinetobacter baumannii Isolates from Tripoli Hospitals - Mohamed Ahmed; Abdulmottaleb Zetrini; Murad Daddesh; Najib Sufya; Hend Shubar; Nada Algrew; Naseem Abu khutwa; Hamza Atiya; Abdulaziz Zorgani; Abdulla Bashein (AlQalam Journal of Medical and Applied Sciences, 2025)
Acinetobacter baumannii is a major nosocomial pathogen, particularly in intensive care units (ICUs), due to its remarkable resistance to multiple antibiotics and its persistence in hospital environments. The occurrence of carbapenem-resistant A. baumannii, often driven by the metallo-β-lactamase genes such as blaIMP and blaVIM, results in a serious clinical threat. In this study, 119 A. baumannii samples were collected from different hospitals in Tripoli, Libya. Real-time PCR revealed that 29 (24.3%) isolates carry the blaIMP gene and 62 (52%) have the blaVIM gene. Phenotypic detection of carbapenemase production revealed that chromogenic media had the highest detection rate (74.7%), followed by the Modified Hodge Test (67%) and E-test (47%). Antimicrobial susceptibility testing showed 100% resistance to ertapenem, cefoxitin, ceftriaxone, ampicillin, and amoxicillin-clavulanate, with high resistance also observed against imipenem (88.2%), meropenem (88.2%), gentamycin (94.9%), ciprofloxacin (94%), and levofloxacin (92.4%). Colistin was the only antibiotic to which all A. baumannii isolates remained sensitive. These findings underscore the high burden of multidrug resistance and the widespread presence of blaVIM and blaIMP genes in A. baumannii isolates in Libya. Improved molecular surveillance, reliable detection methods, and improved antibiotic stewardship are urgently needed to control the spread of these resistant pathogens.